Answer:
<h2>
<u>-1 + √3 or -(1 - 2√3)</u></h2>
Step-by-step explanation:
(1 + √3) (2 - √3) = 2 - √3 + 2√3 - 3 = 2 - 3 - √3 + 2√3 = <u>-1 + √3 or -(1 - 2√3)</u>
Answer:
36 units^2
Step-by-step explanation:
The area of a triangle is 1/2*base*height. Knowing this is just 2 triangles means you solve for 1 triangle, then multiply that by 2
Hey!
So before trying to figure out the equation of the line, lets change -3y+4x = 9 into slope-intercept form:
-3y + 4x = 9
-3y = -4x + 9
y = (4/3)x - 3
Now that you have the equation in slope-intercept form we can find the equation of the line parallel to this. One thing that we are given from this equation is the slope of the line, the slope for two parallel lines are the same. So we know that the slope of the line is 4/3. We are also given another point on the line and we can plug this point in for y and x to find the y-intercept or b:
6 = (4/3)(-12) + b
6 = -16 + b
22 = b
Now that we know b, we have both the y-intercept and the slope so our equation would be:
y = (4/3)x + 22
Answer:
I need a little bit more detail in the question to answer.
Step-by-step explanation:
Answer:
meh
Step-by-step explanation: complicated